Acupuncture therapy for Parkinson’s disease: a case report demonstrating symptomatic improvement without medication - Lei, Suying; Liu, Qing; Leong, IanI; Fan, Jingqi; Tsang, YauKeung; Liu, Xin; Xu, Xiaoyan; Zhuang, Lixing (Frontiers in Neurology, 2024)
Background Parkinson’s disease (PD) often necessitates immediate medical intervention following diagnosis. In recent years, there has been a noticeable increase in clinical investigations assessing the efficacy of acupuncture in PD, with many studies reporting positive outcomes. Ethical guidelines commonly endorse pharmaceutical therapies for PD, leading ongoing research to combine acupuncture with standard drug-based treatments. At present, there is a conspicuous absence of dedicated clinical research exclusively examining the independent impact of acupuncture on PD treatment. Case In a clinical observation, we documented a case involving a 75-year-old male displaying progressive, characteristic PD symptoms, including evident limb tremors, rigidity, bradykinesia, fatigue, and additional non-motor symptoms. The patient received a confirmed diagnosis of PD. Due to the refusal of the patient to take medication, we exclusively administered acupuncture therapy. The outcomes indicated a noteworthy enhancement in the clinical symptoms of the patient solely through acupuncture intervention. Conclusion This case affirms that using acupuncture in isolation significantly improved both the motor and non-motor symptoms in the patient. Acupuncture could potentially serve as an alternative therapy for patients who decline or are intolerant to anti-Parkinson drugs. However, further studies are needed to assess its long-term efficacy. This case report obtained approval from the Ethics Committee of the First Affiliated Hospital of Guangzhou University of Chinese Medicine (Ethics number: K-2023-127).